Creating in the metaverse: An SSRL‐based collaborative painting approach to promote students' creativity, socially shared regulation and positive painting behaviours - Guan, Jue‐Qi; Wang, Xiao‐Feng; Wang, Wen‐Zhuo; Zhu, Jiong; Hwang, Gwo‐Jen (Journal of computer assisted learning, 2024)
Background Painting is the foundational expression across all art forms and is one of the key creative practices for fostering students' aesthetic ability and creativity within fine arts courses. Collaborative painting in the form of socially shared regulation of learning (SSRL) can be recognized as an effective strategy for enhancing creativity in both individual and group work. However, the absence of contextual experiences and collaborative spaces poses challenges for students in cultivating their creativity in painting. Objectives The present study explores students' creativity, socially shared regulation (SSR) and positive painting behaviours using an SSRL‐based collaborative painting approach in the metaverse (Meta‐CP). Methods Via a quasi‐experimental design, a total of 40 Chinese students in fifth grade were recruited and were randomly divided into an experimental group and a control group, with 20 students utilizing the Meta‐CP approach, while the remaining 20 students followed the conventional SSRL‐based paper‐and‐brush collaborative painting (C‐CP) approach. The Meta‐CP approach not only offers an authentic painting context and a collaborative space but also facilitates the collaborative process through the SSRL framework. The data collection included students' creative tendency, painting works and painting process. Results and Conclusions The Meta‐CP approach effectively enhances students' creativity concerning adventure, curiosity and imagination, as well as results in the creation of more distinctive and logical artistic works. Furthermore, the approach significantly improved the quality of students' SSR. Additionally, students utilizing the Meta‐CP approach displayed more positive painting behaviours compared with those employing the C‐CP approach. Lay Description What is already known about this topic: Collaborative painting is an effective strategy for enhancing creativity. Socially shared regulation of learning (SSRL) fosters collaborative learning. Students in collaborative painting may lack a contextual and synchronized painting space. The metaverse benefits in terms of contextual experiences and collaborative spaces. What this paper adds: Using an SSRL‐based collaborative painting approach in the metaverse (Meta‐CP) is effective in improving students' creativity. The Meta‐CP approach has the potential to improve students' quality of socially shared regulation (SSR), and positive painting behaviours. Implications for practice and/or policy: The metaverse provides an immersive synchronized painting space for art education to stimulate students' creative potential. The metaverse with proper learning strategies (e.g., SSRL) provides an effective collaborative learning environment for creation.